Preparation method of carbon-based carbon fiber composite material
By using carbon fiber surface treatment and double-layer coating technology, combined with shear flow field orientation and impregnation process, the corrosion resistance and bonding strength of carbon fiber composite anode plates in fluorinated environments have been solved, improving the overall performance and service life of the material.
Patent Information
- Application Number
- CN202511190148.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-25
- Publication Date
- 2025-11-28
AI Technical Summary
Existing carbon fiber composite anode plates have poor corrosion resistance in fluorinated environments, short service life, easy peeling of coatings, difficulty in orienting fillers, and cannot simultaneously achieve high barrier performance and high interfacial bonding strength.
Low-temperature plasma treatment was used to treat the carbon fiber surface to prepare a double-layer coating. Shear flow field was used to assist the directional arrangement of sheet-like fillers. Dynamic covalent monomer and surface gradient functionalization treatments were used to improve the interfacial bonding strength. Vacuum-pressure impregnation process was combined to improve the material density.
It significantly improves the material's resistance to fluorination, extends its service life, reduces resistivity, increases interfacial bonding strength and electrolysis efficiency, reduces shedding, lowers maintenance costs, and achieves economic benefits.
Smart Images

Figure CN121021179A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of fiber composite materials, and more particularly to a preparation method of carbon-based carbon fiber composite material. BACKGROUND
[0002] The anode material used in the electrolytic fluorine production process is traditionally non-graphitized carbon anode plate. During the electrolysis process, the surface of the anode plate is gradually fluorinated (oxidized), resulting in poor electrical conductivity and poor bending resistance, causing peeling problems, contaminating raw materials, and affecting production efficiency. The currently widely used carbon anode plate has a bulk density of 1.65-1.67 g / cm3, an electrical resistivity of 50-54 mu Omega.m, a bending strength of 35 MPa, and a service life of only 2-4 months.
[0003] The carbon fiber composite anode plate in the prior art mainly has the following technical problems: 1. Poor corrosion resistance in fluorinated environment and short service life; 2. The interface bonding strength between the coated carbon fiber and the carbon matrix is insufficient, causing the coating to easily peel off during use; 3. It is difficult to achieve highly ordered directional arrangement of inorganic sheet-shaped fillers in the coating; 4. There is a difficult-to-coordinate conflict between increased filler content and interface bonding strength; 5. Traditional coating technology cannot simultaneously achieve high barrier performance and high interface bonding strength. SUMMARY
[0004] In order to solve the above technical problems, the present application provides a preparation method of carbon-based carbon fiber composite material, comprising the following steps: Step 1: surface activation treatment of carbon fiber; Step 2: preparation of a double-layer coating on the surface of the carbon fiber, including coating a carbonophilic first layer of film on the surface of the carbon fiber, and then coating a fluorine-resistant second layer of film containing sheet-shaped fillers subjected to surface gradient functionalization treatment on the first layer of film; Step 3: directional arrangement of the sheet-shaped fillers in the second layer of film using a shear flow field; Step 4: preparation of carbon-based paste; Step 5: mixing of the coated carbon fiber and the carbon-based paste and compression molding; Step 6: high-temperature carbonization treatment of the molded body; Step 7: impregnation filling and solidification of the carbonized product.
[0005] Preferably, the surface activation treatment includes: using low-temperature plasma to treat the surface of the carbon fiber to form oxygen-containing functional groups.
[0006] Preferred method: The preparation of the carbon-loving first layer film includes: adding a lipase catalyst to promote the esterification reaction between the oxygen-containing functional groups in the phenolic resin molecule and the functional groups on the carbon fiber surface, and performing a pre-curing reaction at 45-55℃ for 1-2 hours.
[0007] Preferred surface gradient functionalization treatment includes: treating the surface of the sheet-like filler with a silane coupling agent under low temperature conditions, so that the silane coupling agent preferentially binds to the edge region of the filler; and then adding a fluorinated silane treatment agent at room temperature to form anti-fluorination properties on the surface of the central region of the filler.
[0008] Preferably, the shear flow field assistance includes: forming a laminar shear field by controlling the relative rotation speed and shear gap of the coaxial rotating cylinder, so that the sheet packing is arranged along the flow direction to form an oriented layered structure.
[0009] Preferably, a dynamic covalent monomer with a mass fraction of 1-3% is added to the precursor of the second film. The dynamic covalent monomer contains a reversible covalent bond structure that preferentially breaks and absorbs energy when the material is subjected to mechanical stress or chemical corrosion.
[0010] Preferably, the dynamic covalent monomer is selected from dithiodipropionate, 3,4-dihydroxyphenylboronic acid ester or tetraphenylethylene derivative.
[0011] Preferred: The sheet-like filler is selected from one or more of graphene, vermiculite, and montmorillonite, with a particle size of 1-5μm, a thickness of 5-20nm, and an aspect ratio of 50-1000.
[0012] Preferred: The high-temperature carbonization treatment temperature is 1050℃, and a protective gas with low oxygen content is introduced throughout the carbonization process.
[0013] Preferred method: The impregnation filling adopts a vacuum-pressure impregnation process, which includes first evacuating the gas in the pores of the anode plate, then applying positive pressure to make the impregnating agent penetrate into the pores of the anode plate, and finally performing a curing treatment.
[0014] The beneficial effects of this invention are as follows: The physical properties are comprehensively improved, with a 5% increase in bulk density to 1.65-1.75 g / cm³, a 25% decrease in resistivity to 35-45 μΩ·m, and a 50% increase in flexural strength to 45-55 MPa. Fluorination resistance is significantly enhanced, with a 60% reduction in corrosion rate to 0.15-0.2 mm / month, and a service life extended to 8-12 months, 3-4 times that of traditional anode plates. Interfacial bonding strength is increased by approximately 70%, and the retention rate after thermal cycling reaches over 90%. In terms of electrolysis efficiency, current efficiency is increased by 15-20% to 95-98%, and energy consumption is reduced by 10-15% to 12-13 kWh / kg. Anode plate surface shedding is reduced by over 85%, increasing product purity from 99.0-99.2% to 99.5-99.8%. Maintenance costs are reduced by approximately 50%, and production line downtime is reduced by 70%. Although the manufacturing cost is 30% higher, the overall operating cost is reduced by 40-50%, achieving significant economic benefits. Attached Figure Description
[0015] Figure 1 It is a curve showing how the penetration depth of fluorine changes over time; Figure 2 It shows the trend of interfacial bonding strength changing with the number of thermal cycles; Figure 3 This is a curve showing the change in fluoride ion permeability over time. Figure 4 It refers to the energy absorption effect during cyclic tensile testing; Figure 5 It shows the trend of current efficiency over operating time. Detailed Implementation
[0016] The subject matter described herein will now be discussed with reference to exemplary embodiments. It should be understood that these embodiments are discussed only to enable those skilled in the art to better understand and implement the subject matter described herein, and changes may be made to the function and arrangement of the elements discussed without departing from the scope of this specification. Various processes or components may be omitted, substituted, or added as needed in the examples. Furthermore, some features described in the examples may be combined in other examples. Example
[0017] This embodiment proposes a method for preparing carbon-based carbon fiber composite materials, including the following steps: Step 1: Perform surface activation treatment on the carbon fiber; Surface activation treatment includes treating the carbon fiber surface with low-temperature plasma to form oxygen-containing functional groups.
[0018] Step 2: Prepare a double-layer coating on the carbon fiber surface, including coating a carbon-loving first layer film on the carbon fiber surface, and then coating a fluorination-resistant second layer film containing sheet-like fillers with surface gradient functionalization treatment on the first layer film. The preparation of the carbonophilic first layer film includes: adding a lipase catalyst to promote the esterification reaction between the oxygen-containing functional groups in the phenolic resin molecule and the functional groups on the carbon fiber surface, and performing a pre-curing reaction at 50°C for 1.5 hours; The surface gradient functionalization treatment includes: treating the surface of the sheet-like filler with a silane coupling agent under low temperature conditions, so that the silane coupling agent preferentially binds to the edge region of the filler; and then adding a fluorinated silane treatment agent at room temperature to form anti-fluorination properties on the surface of the central region of the filler. A dynamic covalent monomer with a mass fraction of 2% is added to the precursor of the second film. The dynamic covalent monomer contains a reversible covalent bond structure, which preferentially breaks and absorbs energy when the material is subjected to mechanical stress or chemical corrosion. The dynamic covalent monomer is selected from dithiodipropionate; The sheet-like filler is selected from graphene, with a particle size of 3μm, a thickness of 12nm, and an aspect ratio of 500.
[0019] Step 3: Use shear flow field assistance to orient the sheet-like packing material in the second membrane layer; The shear flow field assistance includes: creating a laminar shear field by controlling the relative rotation speed and shear gap of the coaxial rotating cylinder, so that the sheet packing is arranged along the flow direction to form an oriented layered structure.
[0020] Step 4: Prepare carbon-based paste.
[0021] Step 5: Mix the coated carbon fiber with the carbon-based paste and press it into shape.
[0022] Step 6: Perform high-temperature carbonization treatment on the molded body.
[0023] The high-temperature carbonization process is carried out at 1050℃, and a protective gas with low oxygen content is introduced throughout the process.
[0024] Step 7: Impregnate and fill the carbonized product and then cure it; The impregnation filling adopts a vacuum-pressure impregnation process, which includes first evacuating the gas from the pores of the anode plate, then applying positive pressure to allow the impregnating agent to penetrate into the pores of the anode plate, and finally performing a curing treatment. Example
[0025] The difference between this embodiment and Embodiment 1 is that: The preparation of the carbonophilic first layer film includes: adding a lipase catalyst to promote the esterification reaction between the oxygen-containing functional groups in the phenolic resin molecule and the functional groups on the carbon fiber surface, and performing a pre-curing reaction at 55°C for 2 hours. A 3% by mass of dynamic covalent monomer was added to the precursor of the second membrane.
[0026] The dynamic covalent monomer is selected from tetraphenylethylene derivatives; The sheet-like filler is selected from graphene, vermiculite and montmorillonite, with a particle size of 5μm, a thickness of 20nm and an aspect ratio of 1000. Example
[0027] The difference between this embodiment and Embodiment 1 is that: The preparation of the carbonophilic first layer film includes: adding a lipase catalyst to promote the esterification reaction between the oxygen-containing functional groups in the phenolic resin molecule and the functional groups on the carbon fiber surface, and performing a pre-curing reaction at 45°C for 1 hour. A 1% by mass of dynamic covalent monomer was added to the precursor of the second membrane.
[0028] The dynamically covalent monomer is selected from 3,4-dihydroxyphenylboronic acid ester; The sheet-like filler is selected from graphene and vermiculite, with a particle size of 1μm, a thickness of 5nm, and an aspect ratio of 50. Example
[0029] This embodiment presents a method for preparing carbon-based carbon fiber composite materials, which is carried out in the following steps in sequence: 1. Carbon fiber pretreatment The pretreatment process for carbon fibers includes two steps: cutting and surface activation. Carbon fiber cutting: Cutting continuous carbon fiber bundles into short filaments with a length of 3-8 mm for subsequent mixing with carbon matrix materials; Surface activation treatment: The carbon fiber surface is activated using low-temperature plasma, with oxygen as the working gas, plasma power of 50-100W, and processing time of 30-60 seconds. Plasma treatment is carried out at a low pressure of 0.1-0.5 Torr and the treatment temperature does not exceed 200℃ to avoid damaging the carbon fiber structure. Through plasma treatment, oxygen-containing functional groups such as carboxyl, hydroxyl, and ketone groups are formed on the surface of carbon fibers, increasing the number of surface active sites. The oxygen content on the surface of the treated carbon fiber increased from 2-5% to 8-15%, and the surface roughness increased by 30-50%. The activated carbon fibers are rinsed with deionized water 3-5 times and dried under vacuum at 60-80℃ for 4-6 hours to obtain modified carbon fiber short filaments with active functional groups on the surface.
[0030] 2. Preparation of double-layer coating This step creates a double-layer coating structure, resolving the conflict between interfacial bonding strength and fluorination resistance: Preparation of the first coating layer (carbon-loving film layer): A carbonophilic membrane precursor solution was prepared, consisting of phenolic resin (phenolic condensate, molecular weight 2000-3000 Da, mass fraction 40-50%), crosslinking agent (hexamethylenetetramine, mass fraction 3-5%), compatibilizer (polyvinyl alcohol, molecular weight 15000-25000 Da, mass fraction 2-4%) and organic solvent (ethanol / acetone mixed solvent, volume ratio 1:1, balance). Add 0.5-1.5% by mass of lipase catalyst (porcine pancreatic lipase, enzyme activity ≥200U / mg, or recombinant lipase derived from Candida albicans) to promote the esterification reaction between oxygen-containing functional groups (hydroxyl groups, content 10-15mmol / g) in phenolic resin molecules and functional groups on the surface of carbon fibers. The pretreated carbon fibers are immersed in the above solution and ultrasonically dispersed at 25-35℃ for 30-45 minutes to obtain a uniform coated carbon fiber suspension. Using an intermittent vacuum-pressure alternating impregnation process, first evacuate to -0.08MPa and hold for 5-10 minutes, then apply a positive pressure of 0.2-0.5MPa and hold for 10-15 minutes, repeat 3-5 cycles to allow the precursor solution to penetrate into the carbon fiber surface structure. Under the catalysis of bio-enzymes, a pre-curing reaction is carried out at 45-55℃ for 1-2 hours to form a chemically bonded carbonophilic first coating layer with a thickness of 0.2-0.5μm; Preparation of the second coating layer (anti-fluorination film layer): The precursor solution for the anti-fluorination film layer is prepared by comprising epoxy resin (bisphenol A type epoxy resin, epoxy equivalent 180-200 g / eq, mass fraction 30-40%), curing agent (modified polyamide, amine value 350-400 mg KOH / g, mass fraction 5-8%), high temperature flame retardant (ammonium polyphosphate, purity ≥98%, mass fraction 3-5%) and organic solvent (toluene / acetone mixed solvent, volume ratio 2:1, balance). A sheet-like filler (mass fraction 20-30%) with surface gradient functionalization is added to the precursor solution. The filler is selected from inorganic sheet-like materials such as graphene (carbon content >99.5%, specific surface area 500-800m² / g), vermiculite (purity >98%, expansion ≥8ml / g), and montmorillonite (cation exchange capacity 80-120meq / 100g), with a particle size of 1-5μm, a thickness of 5-20nm, and an aspect ratio of 50-1000. The carbon fiber coated with the first layer of film is immersed in the fluoride-resistant film precursor solution, and the coating is carried out using a shear flow field-assisted method (see step 3 for details). After the coating is completed, it is pre-cured at 60-70℃ for 2-3 hours, and then post-cured at 120-150℃ for 1-2 hours to form a dense anti-fluorination second coating layer with a thickness of 0.5-1.0μm; Sacrificial bond formation method: Add 1-3% by mass of dynamic covalent monomers to the second coating precursor, specifically reversible covalent monomers such as dithiodipropionate (breakage energy of about 250 kJ / mol), 3,4-dihydroxyphenylboronic acid ester (breakage energy of about 150-200 kJ / mol), or tetraphenylethylene derivatives (photoresponsive breakage energy of about 180 kJ / mol); Weigh and adjust the mass ratio of crosslinking agent (hexamethylenetetramine or diaminodiphenylmethane) to dynamic covalent monomer to 3:1-5:1 using a precision electronic balance (accuracy 0.001g). Mix for 30-45 minutes using a mechanical stirrer (speed 400-600rpm) to form a molecular system with a stable network structure and repairability. When the coating material is subjected to mechanical stress (stress threshold 2-5 MPa) or chemical corrosion (pH < 3 or > 10), these sacrificial bonds preferentially break and absorb energy (energy absorption efficiency 70-85%), protecting the main chain structure and preventing overall material failure. This process can be observed by infrared spectroscopy (FTIR) with characteristic peaks (e.g., SS bonds at 500-540 cm⁻¹). -1 The intensity of the absorption peak at that location decreases; Once the external stress is removed, the broken sacrificial bonds will automatically reform under specific conditions (heating to 60-80℃ for 1-2 hours, irradiation with 365nm ultraviolet light at an intensity of 5-10mW / cm² for 15-30 minutes, or adjusting the pH value to 7-8 and maintaining it for 4-6 hours), with a repair rate of 80-90% (measured by tensile strength recovery rate), thus realizing the self-healing function of the material and extending its service life.
[0031] 3. Directional arrangement process of sheet packing This step addresses the directional alignment of inorganic sheet-like fillers in film coating: Surface gradient functionalization method: Regionally selective surface modification of sheet-like packings allows the edge and central regions of the packings to have different surface chemical properties. Under low temperature (10-15℃) conditions, the surface of the sheet-like filler is treated with a silane coupling agent (γ-glycidyl ether oxypropyltrimethoxysilane) for 30-40 minutes. The silane coupling agent preferentially binds to the edge area of the filler. At room temperature (20-25℃), a fluorinated silane (1H,1H,2H,2H-perfluorooctyltriethoxysilane) treatment agent is added, and the reaction is carried out for 2-3 hours, forming anti-fluorination properties on the surface of the central region of the filler. The filler is subjected to graded washing, 3-5 times with ethanol and deionized water, and vacuum dried at 60℃ for 8-12 hours to obtain gradient functionalized sheet filler with carbon-loving edges and fluorine-resistant center. Shear flow field auxiliary methods: The Taylor-Couette type shear flow field device (inner diameter 50mm, outer diameter 60mm, height 100mm) is used, including an adjustable speed coaxial rotating cylinder (speed accuracy ±1rpm) and a micron-level gap control system (accuracy 0.01mm). A second-layer coating precursor solution containing gradient functionalized sheet fillers (viscosity 150-250 mPa·s, measurement temperature 25℃) is placed into the annular space of the device, with the filling rate controlled at 85-95%. The relative rotational speed of the inner and outer cylinders (starting at 150 rpm, gradually decreasing to 50 rpm at a rate of 2-5 rpm / min) and the shear gap (0.2-0.5 mm) are precisely controlled by a frequency converter, resulting in a shear rate of 200-500 s. -1 Laminar shear field; Under the action of shear flow field, the sheet packing is driven by shear force (0.05-0.15Pa) to align along the flow direction, forming a layered structure with an orientation degree >85% (measured by polarizing microscope and X-ray diffraction); The shearing process lasts 15-30 minutes, while the shearing rate is gradually reduced according to the preset program (20-30 rpm every 5 minutes) to make the packing more neatly arranged; the temperature should be kept constant at 20-25℃ during the shearing process and controlled by a circulating water bath. Methods for interaction between packing materials: Surface-modifying agents (3-aminopropyltriethoxysilane or sodium carboxymethyl cellulose) are used to add 0.5-1.0% by mass of hydrogen bond donors (hydroxyl, carboxyl, surface density 2-4 bonds / nm²) and acceptor groups (amino, amide, surface density 1-3 bonds / nm²) to the surface of gradient functionalized sheet fillers. When adjacent fillers approach the critical distance (0.3-0.5 nm), a hydrogen bond network (bond energy 5-30 kJ / mol, bond density approximately 1.5-2.5 bonds / nm²) is formed between these groups, causing the fillers to adjust their positions and form a partially overlapping "brick-and-mortar" structure. This process can be verified by molecular dynamics simulation or atomic force microscopy. During the curing process, a programmable temperature controller is used to precisely control the temperature rise rate at 1.0-2.0℃ / min (preferably 1.5℃ / min), allowing the filler sufficient time for thermal adjustment (approximately 15-30 minutes of flow time window). The degree of completion of filler arrangement can be determined by monitoring the position and shape of the exothermic peak during the curing process using differential scanning calorimetry (DSC). In the final structure, the overlap rate of adjacent sheet-like fillers is 40-60% (measured by transmission electron microscopy and small-angle X-ray scattering), forming a fluorine permeation path with a detour factor of 2.5-3.5 (measured by gas permeability), which reduces the fluorine ion permeation rate by 85-95% (compared to the non-directional structure).
[0032] 4. Preparation of carbon-based paste This step involves preparing the carbon-based paste, including the following operations: Raw material preparation: Petroleum coke (fixed carbon content ≥98%, ash content ≤0.5%, volatile matter ≤1.0%, true density 2.1-2.2 g / cm³) is crushed and then ground in a ball mill (250-300 rpm, ball-to-material ratio 3:1). The powder is then sieved using a standard vibrating screen (50 Hz) to obtain fine powder ≤0.074 mm (40-50%, specific surface area 1.5-2.0 m² / g), medium powder 0.074-0.5 mm (30-40%), and coarse powder 0.5-2 mm (10-20%). A mixing ratio of 3:2:1 for these three particle sizes is preferred. Coal tar pitch coke (softening point ≥180℃, fixed carbon ≥85%, volatile matter ≤15%) is crushed into 0.5-2mm particles using a hammer crusher, and metallic impurities are removed by magnetic separation and used as a reinforcing component. Medium-temperature asphalt (softening point 85-100℃, alcohol-benzene insoluble content 20-30%, quinine insoluble content 8-12%) is heated to 150-170℃ in an electric thermostatic drying oven to completely melt it (viscosity 100-150mPa·s) and used as a binder. Ingredients and Mixing: Use a precision electronic scale (accuracy ±0.01g) to mix solid materials and binder at a mass ratio of 85:15 (acceptable range 83:17 to 87:13, preferred 85:15); In the solid materials, petroleum coke powder accounts for 80-90% (the three particle sizes are mixed in the aforementioned proportions), and coal tar pitch coke accounts for 10-20%; the particle size distribution is optimized based on the principle of meeting the maximum bulk density and is determined by the tapped density test (GB / T 8074); Melted medium-temperature asphalt (temperature controlled at 155-165℃) is poured into a stainless steel container preheated to 150℃ into a forced mixer (with a σ-type rotor, speed 20-30 rpm) preheated to 130-150℃. Solid materials are gradually added to the mixer (feeding speed controlled at 2-3 kg / min), while the rotor is continuously stirred (speed not less than 25 rpm), and the material temperature is maintained at 130-140℃ to ensure uniform mixing; the uniformity of mixing is determined by sampling and testing the consistency of binder distribution (coefficient of variation <5%). Kneading operation: Transfer the mixture to a double Z-type vacuum kneader (power 15-20kW, volume 50-100L), and knead it at a temperature of 130-150℃ (controlled by an electric heating mantle, temperature fluctuation ≤±2℃) and a speed of 20-30rpm. The kneading process lasts 45-60 minutes (too short a kneading time will result in uneven mixing, while too long a time will result in oxidative degradation of the binder). When the rotor torque reaches a stable value (fluctuation <5%), it indicates that the binder has uniformly coated the surface of each particle size of carbon material. The kneading quality can be evaluated by observing the uniformity of the coating on the particle surface under a microscope or by extracting samples to test their compressive strength (which should reach 3-5 MPa). The kneading process maintains a vacuum of -0.05 MPa or higher (monitored by a vacuum pressure gauge) throughout, reducing the air bubble content to below 0.5% and preventing the binder from oxidizing. After kneading, the carbon-based paste is transferred to a non-stick coating cooling tray and allowed to cool naturally at room temperature (25±5℃) to below 40℃ (about 4-6 hours). It is then crushed into uniform particles of 5-10mm using a mechanical crusher, sieved to remove powdery substances, and sealed for later use. A qualified paste should have a glossy surface and a certain degree of plasticity. The crushed particles should pass through a 5mm standard sieve but be retained by a 10mm standard sieve.
[0033] 5. Mold forming This step combines the coated carbon fiber with carbon-based paste to form the anode plate blank: Mold preparation: Select a 45# steel mold (wall thickness 10-15mm, surface hardness HRC40-45) suitable for the anode plate size. It is generally rectangular with a standard size of 300×200×50mm (which can be adjusted within ±15% according to actual needs). The inner cavity is precision ground with a surface roughness Ra≤0.8μm. A release agent (a mixture of high-quality graphite powder and anhydrous ethanol in a 1:3 mass ratio, with a coating thickness of 0.05-0.1 mm) is uniformly applied to the inner wall of the mold. The uniformity of the coating is confirmed by visual inspection to ensure that there are no missed areas or uneven thicknesses, which facilitates the demolding of the anode plate. The mold is preheated to 80-100℃ using an electric heating system (temperature uniformity ±5℃ is monitored by thermocouples) to reduce the temperature gradient during the filling process and prevent cracks caused by thermal stress. Composite structure paving: Using specialized measuring tools, evenly spread a 3-5mm thick layer of carbon-based paste at the bottom of the mold as the base layer, and lightly press it with specialized tamping tools to obtain a pre-compacted density of 85-90% (calculated by measuring the height and weight). The coated carbon fibers are laid on the bottom paste in a preset arrangement pattern (cross or parallel arrangement, with a spacing of 5-8 mm). The amount of coated carbon fibers added is controlled to be 5-15% (preferably 8-12%) of the total material mass. The fiber content can be determined by the ignition method (GB / T 2577). The structure adopts a "sandwich" structure, which is an alternating laying method of paste-coated carbon fiber-paste, laying 3-5 layers of coated carbon fiber, and maintaining the paste thickness between each layer at 8-12mm (controlled by measuring with calipers). The fiber orientations in adjacent coated carbon fiber layers are perpendicular to each other (90°±5°), forming an orthogonal structure. The fiber arrangement angle is confirmed by an optical measuring instrument, which increases the anisotropic strength of the material. The flexural strength anisotropy ratio is controlled within 1:1.2. Cover the top with a 5-8mm thick carbon-based paste and flatten it with a flat tool. Control the compaction degree to 85-90% and the surface flatness deviation to ≤1mm / m to complete the mold filling. Vibration exhaust: Place the filled mold on a vibration table with a power of 2-5kW and vibrate it at a low frequency (30-50Hz) for 5-8 minutes, with the amplitude controlled at 0.5-1.0mm. During vibration, use a rubber hammer (500-800g) to gently tap the side wall of the mold from the edge to the center to expel internal air bubbles; the air bubble content can be detected by an ultrasonic detector and controlled to be below 1%; After vibration, apply a uniform pressure of 0.5-1.0 MPa to the top of the mold for 1-2 minutes to make the material surface flat, with the flatness deviation controlled within 0.5 mm.
[0034] 6. Pressing and heat treatment This step involves compression molding and high-temperature carbonization: Hot pressing: Place the mold filled with material into a four-column hydraulic hot press (pressure capacity 1000-1500 tons, plate size 500×500mm, temperature control accuracy ±2℃), and preheat the press plate to 120-140℃. At a temperature of 120-140℃, a multi-stage pressurization process is adopted: first, a pre-compression of 5MPa is applied for 5 minutes to release internal stress, and then the pressure is gradually increased to 15-25MPa (preferably 20MPa) at a rate of 5MPa / min, and maintained for 30-45 minutes (30 minutes for material thickness <50mm, 45 minutes for ≥50mm); the uniformity of pressure distribution is ensured to be <10% by pressure-sensitive paper testing; During the pressing process, the binder softens and flows under the action of heat, filling the gaps between the carbon material and the carbon fiber. The material temperature is maintained at 125-135℃ by monitoring with an embedded thermocouple, which increases the material density. The material flowability can be observed through the pre-set flow indicator groove in the mold. The density of the pressed blank reaches 1.50-1.55 g / cm³ (determined by Archimedes' displacement method, GB / T 1998), and the porosity is reduced to 10-15% (determined by mercury porosimetry, GB / T 21650.1). First, maintain the pressure and cool down to below 80℃, then slowly release the pressure (1-2MPa / min), and finally cool to room temperature (20-30℃) before demolding to obtain the anode plate blank; the geometric dimensional tolerance of the finished product is controlled within ±1mm, and there are no obvious defects on the surface (confirmed by visual inspection). High-temperature carbonization treatment: The anode plate blank is placed in a box-type high-temperature calcining furnace (temperature uniformity ±10℃, maximum temperature 1200℃), and completely covered with high-purity refractory material (Al2O3 content ≥95%) with a thickness of not less than 20mm to ensure air isolation; the charge density inside the furnace is controlled at 0.6-0.8g / cm³. The roasting process is carried out according to the following precisely controlled temperature rise curve (via a PLC control system): From room temperature to 200℃, the heating rate is 1-2℃ / min (preferably 1.5℃ / min), and the temperature is maintained for 2 hours. This stage mainly removes residual moisture and low-boiling-point organic matter from the material (weight loss of about 2-3%). The temperature is increased from 200℃ to 600℃ at a rate of 0.5-1℃ / min (preferably 0.8℃ / min), and the temperature is maintained for 3 hours. This stage mainly achieves the pre-carbonization of the adhesive (weight loss of about 15-20%). The temperature is increased from 600℃ to 1050℃ at a rate of 1-1.5℃ / min (preferably 1.2℃ / min), and the temperature is held for 5 hours. During this stage, the material is fully carbonized (resistivity decreases by about 30-40%). Throughout the calcination process, the flow of a protective gas (high-purity nitrogen, purity ≥99.99%, or high-purity argon, purity ≥99.999%) with a low oxygen content (≤0.1%, monitored by an oxygen content analyzer) is precisely controlled using a mass flow meter at a flow rate of 0.5-1.0 L / min·kg (based on material mass) to prevent oxidation; the degree of carbonization should reach ≥85% as determined by Raman spectroscopy. After roasting, the temperature is controlled to cool naturally to below 400℃ (about 8-12 hours) according to the program, and then cooled to room temperature at a cooling rate of no more than 50℃ / h (preferably 30-40℃ / h) to prevent cracking caused by thermal stress (the absence of internal cracks is confirmed by ultrasonic non-destructive testing). The carbonized anode plate has a density of 1.40-1.45 g / cm³ (determined by Archimedes' water displacement method), a resistivity of 65-75 μΩ·m (determined by four-probe method), a porosity of 20-25% (determined by mercury porosimetry), and a residual volatile matter content of ≤0.5% (determined by TGA).
[0035] 7. Impregnation and filling This step improves the density and performance of the anode plate through an impregnation process: Preparation for soaking: The impregnation agent is prepared by combining phenolic resin (formaldehyde:phenol molar ratio 0.8-1.2, molecular weight 1500-2500 Da, solid content 70-80%) and organic solvent (methanol and acetone mixed solvent, volume ratio 2:1, mass fraction 20-30%, purity ≥99.5%). Optionally, 0.5-1.0% of a curing catalyst (p-toluenesulfonic acid or hexamethylenetetramine) can be added to accelerate subsequent curing. Use a rotational viscometer (accuracy ±1%) to measure and adjust the impregnating agent to a suitable viscosity (80-120 mPa·s at 25°C, preferably 100 mPa·s); adjust by adding solvent or concentration (vacuum rotary evaporation, 40-50°C, -0.08 MPa); determine the resin solids content (drying method, ISO 3251) to ensure it is within the specified range. The carbonized anode plate is preheated to 60-80℃ (preferably 70℃, ensuring temperature uniformity ±5℃) in a ventilated drying oven at a heating rate of 1-2℃ / min. At the same time, it is vacuum dried for 2-3 hours to ensure that there is no moisture in the pores, increase capillary permeability, and facilitate the penetration of impregnating agent. Vacuum-pressure impregnation: Place the preheated anode plate into a stainless steel high-temperature impregnation tank (lined with polytetrafluoroethylene, pressure resistant 1.0MPa, and volume 3-5 times larger than the anode plate), and completely immerse it in the pre-filtered (5μm filter membrane) and preheated impregnating agent to 40-50℃. The impregnating agent level should be at least 50mm above the top surface of the anode plate. Use a two-stage rotary vane vacuum pump (pumping speed 15-20 m³ / h) to evacuate to above -0.095 MPa (residual pressure ≤0.5 kPa, monitored with a precision vacuum gauge), and maintain for 2-3 hours (the time depends on the porosity and thickness of the anode plate; for every 5% increase in porosity, the holding time increases by 0.5 hours). Confirm that the gas in the pores of the anode plate has been completely removed by observing the bubble discharge. While maintaining a vacuum, the temperature of the impregnating agent is slowly increased (2-3℃ / min) to 80-100℃ (preferably 90℃) through a jacket heating system, reducing the viscosity of the impregnating agent to 30-50 mPa·s and improving the penetration performance; the temperature is monitored by a PT100 sensor with an accuracy of ±1℃. Slowly release the vacuum (0.01 MPa / min), then apply a uniform positive pressure of 0.5-0.8 MPa using a hydraulic system (pressure sensor monitoring, accuracy ±0.02 MPa), and maintain this pressure for 4-6 hours (increase by 0.5 hours for every 10 mm increase in anode plate thickness) to allow the impregnating agent to fully penetrate the pores of the anode plate; the impregnation depth is detected by fluorescent dye tracer method and should reach the center of the anode plate; Curing and post-treatment: After impregnation, the anode plates are removed from the impregnation tank. Excess impregnating agent on the surface is recovered by centrifugation (300-500 rpm, 1-2 minutes) or scraping. Then, they are placed in a precision programmable temperature-controlled oven and heated to 80-100℃ at a heating rate of 1℃ / min for 4-6 hours for pre-curing. During this stage, solvent evaporation and preliminary cross-linking are achieved (gel content reaches 30-40%, determined by Soxhlet extraction). Continue heating at a rate of 1-2℃ / min to 150℃, hold for 2-3 hours to complete the cross-linking of the resin (gel content reaches 70-80%). Finally, raise the temperature to 250-350℃ at a rate of 2℃ / min (select according to the type of resin used; 300-350℃ for phenolic resin and 250-300℃ for epoxy resin) for final curing, and keep at the temperature for 3-4 hours to achieve complete curing and partial carbonization of the resin (curing degree ≥95%, confirmed by measuring residual heat release by differential scanning calorimetry). After curing, the surface is naturally cooled to room temperature at a cooling rate not exceeding 30℃ / h, and then the surface is machined (grinding or milling) to the required dimensions (tolerance ±0.5mm) to obtain the finished carbon-based carbon fiber composite anode plate. Physical properties of the finished anode plate: bulk density 1.65-1.75 g / cm³ (measured by Archimedes method, GB / T 1998), resistivity 35-45 μΩ·m (measured by four-probe method, GB / T 1996), flexural strength ≥45 MPa (measured by three-point bending method, GB / T 1999), closed-cell rate ≥85% (measured by mercury porosimetry), coefficient of thermal expansion 4-6 × 10⁻⁶. -6 / K (measured by a thermal expansion meter in the range of 20-200℃).
[0036] Experimental Example Experiment 1: Fluorination Resistance Test The antifluorination performance of the carbon-based carbon fiber composite anode plate prepared in Example 4 was evaluated in a simulated environment of electrolytic fluorination process and compared with that of a conventional anode plate.
[0037] Experimental materials The carbon-based carbon fiber composite anode plate (sample A) prepared by the method in Example 4. Traditional uncoated carbon anode plate (control sample B); Hydrofluoric acid solution (40-45% concentration); Simulated electrolytic cell (with constant temperature control system and DC power supply).
[0038] Experimental steps Sample preparation: Sample A and Sample B were processed to the same size (50mm×50mm×10mm), and the precise dimensions were measured using digital calipers and the initial mass was measured using an analytical balance.
[0039] Surface scanning: The initial surface morphology of the two samples was observed and recorded using a scanning electron microscope.
[0040] Simulated electrolysis conditions settings: Hydrofluoric acid concentration: 40-45%; Temperature: 90-100℃ (controlled by a constant temperature water bath); Current density: 1.0 kA / m²; Samples A and B were fixed as the anodes of the simulated electrolytic cell and connected to a DC power supply.
[0041] The electrolysis system was run continuously, and samples were taken out every 7 days, rinsed with deionized water, dried at 105°C to constant weight, and the mass loss and dimensional changes were measured.
[0042] The surface morphology changes of the samples were observed using scanning electron microscopy, and the changes in surface elemental composition were analyzed using X-ray photoelectron spectroscopy.
[0043] The test lasted for 90 days, and data from each measurement was recorded.
[0044] Experimental results The corrosion performance of sample A and sample B under simulated electrolysis conditions is compared in the table below:
[0045] The experimental results show that after 90 days of testing: 1. The mass loss rate of sample A (the anode plate of the present invention) was 4.2%, while the mass loss rate of sample B (the conventional anode plate) was as high as 12.5%, a reduction of approximately 66.4%.
[0046] 2. The surface corrosion depth of sample A is 0.43 mm, and the surface corrosion depth of sample B is 1.32 mm, with the corrosion depth decreasing by approximately 67.4%.
[0047] 3. The fluorine penetration depth of sample A was 0.48 mm, while that of sample B was 1.85 mm, representing a decrease in penetration depth of approximately 74.1%.
[0048] Scanning electron microscopy revealed that sample A maintained a relatively intact surface structure with few microcracks, while sample B exhibited numerous erosion pits and a network of cracks, indicating severe damage to its surface structure. X-ray photoelectron spectroscopy analysis showed that the fluorine content on sample A was significantly lower than that on sample B, confirming that the double-layer coating structure and the oriented sheet-like filler effectively blocked the permeation of fluorine.
[0049] Figure 1 The curves show how the fluorine penetration depth changes over time.
[0050] Experiment 2: Interface Bond Strength Test Experimental Objective The effect of the carbonophilic first layer film and bio-enzyme catalytic assisted polymerization technology on improving the bonding strength of the carbon fiber-carbon matrix interface in the preparation method of Example 4 was evaluated, and the bonding strength stability under multiple thermal cycling conditions was verified.
[0051] Experimental materials Example 4: Double-layer coated carbon fiber composite anode plate (sample A) prepared by the method. Traditional single-layer coated carbon fiber composite anode plate (without bio-enzyme catalysis technology, control sample B); Uncoated carbon fiber composite anode plate (control sample C); Materials mechanics testing system (with shear strength testing function); Thermal cycling test chamber (temperature range -40℃ to 200℃); Scanning electron microscope and energy dispersive spectroscopy system.
[0052] Experimental steps Sample preparation: Sample A: Prepared according to the method of the present invention, comprising a carbophilic first layer membrane and an antifluorination second layer membrane, using a lipase catalyst; Sample B: The preparation process is the same as that of Sample A, but without the addition of lipase catalyst; Sample C: Carbon fiber composite anode plate without any coating treatment; All samples are 100mm × 25mm × 5mm in size.
[0053] Initial interface bonding strength test: The interfacial bond strength of the samples was tested using the ASTM D3163 shear strength test method. Perform 10 repeated tests for each sample and calculate the mean and standard deviation; The interface morphology was observed using a scanning electron microscope.
[0054] Thermal cycling test: Place the sample into the thermal cycling test chamber; Set the thermal cycling conditions as follows: -20℃ for 15 minutes → heat up to 80℃ and hold for 15 minutes → cool down to -20℃, one cycle takes 45 minutes; Thermal cycling tests were conducted for 1000, 3000, and 5000 cycles respectively. Interfacial bonding strength test after thermal cycling: After the thermal cycling is completed, test the interfacial bonding strength again using the method in step 2. Calculate the strength retention rate before and after thermal cycling; The changes in interface morphology after thermal cycling were observed using a scanning electron microscope.
[0055] Peeling performance test: The interfacial peel work was determined using the ASTM D5528 test method. Perform five repeated tests on each sample and calculate the average value.
[0056] Experimental results The interfacial bonding strength test results for different samples are shown in the table below:
[0057] Scanning electron microscopy observations show: 1. Sample A (this invention): The interface is tightly bonded, and a clear chemical bonding interface is formed between the coating layer and the carbon fiber. After 5000 thermal cycles, the interface structure remains basically intact with only a few microcracks.
[0058] 2. Sample B (single-layer coating): The interfacial bonding is relatively loose, mainly relying on physical adsorption force. After 5000 thermal cycles, obvious interfacial cracks and local peeling appeared.
[0059] 3. Sample C (without coating): The interfacial bonding was the worst, and large-area peeling and crack propagation occurred after 5000 thermal cycles.
[0060] Energy dispersive spectroscopy (EDS) analysis showed that the CO bond content in the interfacial region of sample A was significantly higher than that of samples B and C, confirming that enzyme-assisted polymerization promoted the esterification reaction and formed a strengthened chemically bonded interface. Furthermore, sample A showed the least change in elemental distribution in the interfacial region after thermal cycling, indicating the best interfacial structural stability.
[0061] Figure 2 The trend of interfacial bonding strength with the number of thermal cycles is shown.
[0062] Experimental results show that the interfacial bonding strength of the carbon-based carbon fiber composite anode plate (sample A) prepared by this invention is significantly higher than that of the control sample. The initial interfacial bonding strength is about 48.4% higher than that of sample B and about 96.6% higher than that of sample C. More importantly, sample A still maintains 92.0% of its interfacial bonding strength after 5000 thermal cycles, while the strength retention rates of samples B and C are only 75.5% and 58.6%, respectively. This proves that the carbon-loving first layer film and the bio-enzyme catalytic assisted polymerization technology used in this invention significantly improve the bonding strength and thermal stability of the carbon fiber-carbon matrix interface.
[0063] Experiment 3: Test on the directional arrangement effect of sheet packing Experimental Objective The effect of the shear flow field-assisted technology in Example 4 on the directional arrangement of the sheet packing was evaluated, its ability to form a tortuous fluorine permeation path was verified, and the influence of the directional arrangement of the sheet packing on the barrier performance was determined.
[0064] Experimental materials Example 4: A coating layer containing oriented sheet-like fillers prepared by the method (Sample A, treated with shear flow field assisted technology). A coating layer of non-directionally arranged sheet-like filler prepared by conventional methods (sample B, after stirring and mixing). Pure resin coating without sheet fillers (sample C, control group); Transmission electron microscopy (TEM); Small-angle X-ray scattering instrument (SAXS); Fluoride ion permeation testing device; Environmental scanning electron microscopy (ESEM).
[0065] Experimental steps Sample preparation: Sample A: Processed according to the method of this invention using shear flow field assisted technology, with a shear rate of 300 s. -1 Processing time: 25 minutes; Sample B: Using conventional stirring and mixing techniques, the speed was 400 rpm, and the mixing time was 25 minutes; Sample C: Pure resin coating without any added flake fillers; All samples were prepared as thin films measuring 50 mm × 50 mm × 0.5 mm; Determination of the orientation of sheet packing: The arrangement of the sheet-like packing material was observed using a transmission electron microscope; The orientation distribution of the filler was determined using small-angle X-ray scattering. Calculate the orientation parameter (f) to evaluate the orientation of the filler; The overlap rate of adjacent fillers was measured using image analysis software.
[0066] Determination of detour factor: The porosity and pore size distribution of the samples were determined using mercury porosimetry. The effective diffusion coefficient was determined using the Knudsen gas diffusion method. Calculate the detour factor τ = ε·D0 / D e (ε is porosity, D0 is free space diffusion coefficient, D...) e (Effective diffusion coefficient).
[0067] Fluoride ion permeability test: Using a homemade osmosis testing device, one side contains a fluoride solution (1 mol / L NaF solution), and the other side contains pure water; The test was conducted at 25°C for 24 hours, with samples collected every 4 hours to determine the fluoride ion concentration. The concentration of fluoride ions passing through the sample was determined using a fluoride ion selective electrode. Calculate the fluoride ion permeation rate and the barrier effect.
[0068] Microstructure observation: The microstructure of the sample cross section was observed using ESEM; Analyze the influence of packing arrangement on microstructure; Measure the packing spacing and arrangement angle.
[0069] Experimental results The test results of the directional arrangement of the sheet packing are shown in the table below:
[0070] The results of transmission electron microscopy showed that: 1. Sample A: The sheet-like packing material is arranged in a highly parallel manner, with obvious overlapping areas between adjacent packing materials, forming a layered structure similar to a "brick wall".
[0071] 2. Sample B: The sheet-like packing material is randomly arranged with a random orientation, little overlap, and a large number of straight channels.
[0072] 3. Sample C: No sheet filler, only homogeneous resin matrix.
[0073] Small-angle X-ray scattering (SAXS) measurements showed that the f-value of the sheet-like filler in sample A was 0.88, indicating a high degree of orientation; while the f-value of sample B was only 0.32, indicating a low degree of orientation. Environmental scanning electron microscopy further confirmed that the sheet-like filler in sample A was arranged parallel to the film surface, with uniform interlayer spacing and an orderly arrangement.
[0074] Figure 3 The curve showing the change in fluoride ion permeability over time is presented.
[0075] Experimental results show that the shear flow field-assisted technology used in this invention can significantly improve the directional alignment of the sheet-like packing material. Sample A exhibits a high directional packing material orientation of 88.5% and an overlap rate of 52.3% between adjacent packing materials, far exceeding that of Sample B prepared using traditional methods. This highly oriented "brick wall" structure forms a complex, circuitous permeation path, forcing fluoride ions to detour, significantly extending the permeation path and improving the barrier effect. 24-hour testing results show that the fluoride ion permeation of Sample A is only 21.2% of that of Sample B, with a fluoride ion barrier rate increased by 25.3 percentage points, proving that the shear flow field-assisted orientation technology of this invention can effectively construct a highly efficient fluoride barrier structure.
[0076] Experiment 4: Sacrificial Bond Protection Mechanism Test Experimental Objective The invention aims to verify the protective mechanism of the sacrificial bond formed by the dynamic covalent monomer introduced in this invention when the material is subjected to mechanical stress or chemical corrosion, and to evaluate its fracture energy absorption and self-healing ability.
[0077] Experimental materials The sacrificial bond-containing coating layer prepared by the method in Example 4 (Sample A, containing disulfide monomer, mass fraction 2.5%). Control sample (sample B, conventional coating without sacrificial bonds); Mechanical property testing system (including in-situ microscopic observation device); Raman spectrometer (used to monitor changes in chemical bonds); Fluoride corrosion solution (45% HF solution); Material repair equipment (including temperature control, lighting and pH adjustment systems).
[0078] Experimental steps Sample preparation: Sample A: According to the method of the present invention, dithiodipropionate (2.5% by mass) was added as a sacrificial bond monomer to the second coating precursor; Sample B: The preparation process is the same as that of Sample A, but without the addition of sacrificial monomers; All samples were prepared as dumbbell-shaped specimens in accordance with ASTM D638.
[0079] Cyclic tensile testing and mechanical energy absorption assessment: Cyclic tensile tests were performed using a mechanical property testing system. Loading conditions are set as follows: strain rate 0.5 mm / min, maximum tensile strain 5%; Perform 10 load-unload cycles and record the load-displacement curves; Calculate the energy absorption (hysteresis loop area) for each cycle. In-situ microscopic observation devices are used to monitor the formation and development of microcracks.
[0080] Performance evaluation after chemical corrosion: Immerse the sample locally in 45% HF solution for 15 minutes; Rinse with deionized water and dry; Test the changes in tensile strength and elongation before and after corrosion; The microstructure of the corroded area was observed using a scanning electron microscope.
[0081] Real-time Raman spectroscopy monitoring: In-situ Raman spectroscopy was used to monitor the SS bonds (approximately 500-540 cm⁻¹) during the stretching process. -1 Changes in (location); Record the degree of sacrificial bond breakage under different strain levels; Quantitatively calculate the relationship between the fracture rate of SS bonds and the applied stress.
[0082] Self-healing performance evaluation: The damaged sample was placed under the following repair conditions: Heat repair: 70℃, maintain for 1.5 hours; Phototherapy: Irradiation with 365nm ultraviolet light, intensity 8mW / cm², for 20 minutes; pH restoration: Soak in buffer solution with pH=7.5 for 5 hours; After repair, mechanical property tests were conducted again to calculate the strength recovery rate. Raman spectroscopy was used to confirm the reformation of the SS bonds.
[0083] Experimental results The comparison of the mechanical damage absorption and repair performance of sample A and sample B is shown in the table below:
[0084] Raman spectroscopy analysis showed that the breakage rate of SS bonds in sample A during stretching was linearly related to the applied stress. Significant breakage of the SS bonds began to be observed when the stress reached approximately 3.0 MPa (characteristic peak intensity decreased by about 15%). When the stress reached 4.5 MPa, the SS bond breakage rate reached approximately 65%, while the main chain structure of the resin matrix remained largely intact. During the self-healing process, the recovery of the characteristic peaks of the SS bonds was clearly observed, with the best thermal repair effect, where the peak intensity could be restored to approximately 90% of its original value.
[0085] Figure 4 The energy absorption effect in cyclic tensile testing is demonstrated.
[0086] Experimental results show that the sacrificial bond-containing coating layer (sample A) prepared in this invention exhibits excellent protective and self-healing properties under mechanical damage and chemical corrosion conditions. This is mainly reflected in the following aspects: The initial damage strain of sample A (2.85%) was significantly higher than that of sample B (1.25%), indicating that the introduction of sacrificial bonds improved the toughness and load-bearing capacity of the material.
[0087] In the cyclic tensile test, the energy absorption efficiency of sample A (78.5%) was much higher than that of sample B (42.3%), indicating that the sacrificial bond can effectively absorb external mechanical energy and protect the main structure of the material.
[0088] Raman spectroscopy analysis confirmed that during the stress application process, the sacrificial SS bonds preferentially broke, protecting the main chain structure of the resin matrix and significantly reducing the microcrack density (3.2 cracks / mm² for sample A and as high as 12.5 cracks / mm² for sample B).
[0089] Chemical corrosion tests showed that sample A, containing sacrificial bonds, retained 85.2% of its strength after HF corrosion, while sample B retained only 52.7%, indicating that the sacrificial bond structure can effectively mitigate the damage caused by chemical corrosion.
[0090] The self-healing test results showed that sample A exhibited good strength recovery ability under all three repair conditions, especially under the thermal repair condition, the strength recovery rate reached as high as 88.7%, while sample B, without sacrificial bonds, showed very poor repair performance. This confirms the reversibility and self-healing function of the sacrificial bonds in this invention.
[0091] The above results fully demonstrate that the dynamic covalent sacrificial bond mechanism introduced in this invention can effectively protect materials, extend their service life, and improve their damage resistance and self-repair capabilities.
[0092] Experiment 5: Electrolysis Efficiency Test Experimental Objective The electrolysis efficiency of the carbon-based carbon fiber composite anode plate prepared in this invention in the electrolytic fluorine production process was evaluated, its energy consumption level and product purity were measured, and it was compared with that of a conventional anode plate.
[0093] Experimental materials Carbon-based carbon fiber composite anode plate (sample A) prepared by the method of the present invention. Traditional uncoated carbon anode plate (control sample B); Pilot-scale electrolytic cell (capacity 400 kg / d); Electrolyte (a mixture of hydrogen fluoride and potassium fluoride, molar ratio 1:2); Current efficiency measurement system (including high-precision ammeter and flow meter); Fluoride product purity analysis equipment (gas chromatograph, purity ≥99.99%). Energy consumption monitoring system (power meter).
[0094] Experimental steps Electrolytic cell preparation: Clean and install the pilot electrolytic cell, configuring it according to standard process conditions; Two sets of electrolytic cells were respectively equipped with sample A and sample B as anodes; The effective area of the anode is 0.5m², and the distance between the anode and cathode is maintained at 25mm. The electrolyte temperature is controlled at 85±2℃.
[0095] Electrolysis test procedure: The current density is set to 1.0 kA / m². The electrolytic cell was run continuously, with each 8-hour test cycle. Run continuously for 30 days, recording data for each cycle; Fluoride product samples are collected daily for purity analysis.
[0096] Current efficiency measurement: Measure the input current value I (A); Measure the output fluorine gas flow rate Q (L / h); Calculate the current efficiency η = Qactual / Qtheoretical × 100%; The current efficiency is calculated every 8 hours.
[0097] Energy consumption monitoring: Record the voltage U (V) and current I (A) of the electrolytic cell; Measure the output mass of the product, m (kg). Calculate the energy consumption per unit product E = U×I×t / m (kWh / kg); Energy consumption data is collected daily.
[0098] Product purity analysis: Collect fluorine gas product samples; Gas chromatography was used to analyze the purity and impurity composition of the product. Record the product purity and the content of major impurities.
[0099] Experimental results The performance comparison of samples A and B during the electrolysis process is shown in the table below:
[0100] Figure 5 The trend of current efficiency over operating time is shown.
[0101] Experimental results show that the carbon-based carbon fiber composite anode plate (sample A) prepared in this invention exhibits significantly better performance than the traditional anode plate (sample B) in the electrolytic fluorine production process: Current efficiency: The average current efficiency of sample A is 96.5%, which is 12.3 percentage points higher than that of sample B (84.2%), representing an improvement of 14.6%. More importantly, the current efficiency of sample A decreased by only about 0.5 percentage points during 30 days of operation, while that of sample B decreased by about 2.5 percentage points, indicating that the anode plate of the present invention has better performance stability.
[0102] Energy consumption level: The average energy consumption of sample A is 12.4 kWh / kg, which is 2.4 kWh / kg lower than that of sample B (14.8 kWh / kg), resulting in energy savings of 16.2%. As the operating time increases, the energy consumption growth rate of sample A is significantly lower than that of sample B, indicating that the anode plate of the present invention can maintain a low energy consumption level during long-term operation.
[0103] Product purity: The fluorine gas produced using sample A had an average purity of 99.65%, while sample B had a purity of 99.15%. More importantly, the impurity content (mainly carbon particles and oxides) in the product produced using sample A was only 3450 ppm, which was 59.4% lower than the 8500 ppm of sample B, indicating a significant improvement in product quality.
[0104] Anode loss: After 30 days of operation, the surface loss of sample A was only 0.18 mm, while that of sample B reached 0.46 mm, a reduction of 60.9%. The anode resistance increase rate of sample A was only 4.8%, far lower than that of sample B (15.2%), indicating that the anode plate of the present invention has better structural stability and conductivity during electrolysis.
[0105] Electrolyte contamination: In the electrolytic cell using sample A, the carbon particle content in the electrolyte was only 0.15 g / L, while in the electrolytic cell using sample B, the carbon particle content was as high as 0.82 g / L, a reduction of 81.7%. This indicates that the anode plate of the present invention significantly reduces anode material shedding and effectively reduces electrolyte contamination.
[0106] In summary, the carbon-based carbon fiber composite anode plate prepared by this invention has significant technical advantages and economic benefits in the electrolytic fluorine production process. It not only improves production efficiency and reduces energy consumption, but also extends equipment life and improves product quality.
[0107] The embodiments of the present invention have been described above. However, the embodiments are not limited to the specific implementation methods described above. The specific implementation methods described above are merely illustrative and not restrictive. Those skilled in the art can make more equivalent embodiments under the guidance of the present embodiments, and all of them are within the protection scope of the present embodiments.
Claims
1. A method for preparing a carbon-based carbon fiber composite material, characterized in that, Includes the following steps: Step 1: Perform surface activation treatment on the carbon fiber; Step 2: Prepare a double-layer coating on the carbon fiber surface, including coating a carbon-loving first layer film on the carbon fiber surface, and then coating a fluorination-resistant second layer film containing sheet-like fillers with surface gradient functionalization treatment on the first layer film. Step 3: Use shear flow field assistance to orient the sheet-like packing material in the second membrane layer; Step 4: Prepare carbon-based paste; Step 5: Mix the coated carbon fiber with the carbon-based paste and press it into shape; Step 6: Perform high-temperature carbonization treatment on the molded body; Step 7: Impregnate and fill the carbonized product and then cure it.
2. The preparation method according to claim 1, characterized in that, The surface activation treatment includes: treating the carbon fiber surface with low-temperature plasma to form oxygen-containing functional groups.
3. The preparation method according to claim 1, characterized in that, The preparation of the carbonophilic first layer film includes: adding a lipase catalyst to promote the esterification reaction between the oxygen-containing functional groups in the phenolic resin molecule and the functional groups on the carbon fiber surface, and performing a pre-curing reaction at 45-55℃ for 1-2 hours.
4. The preparation method according to claim 1, characterized in that, The surface gradient functionalization treatment includes: treating the surface of the sheet-like filler with a silane coupling agent under low temperature conditions, so that the silane coupling agent preferentially binds to the edge region of the filler; and then adding a fluorinated silane treatment agent at room temperature to form anti-fluorination properties on the surface of the central region of the filler.
5. The preparation method according to claim 1, characterized in that, The shear flow field assistance includes: forming a laminar shear field by controlling the relative rotation speed and shear gap of the coaxial rotating cylinder, so that the sheet packing is arranged along the flow direction to form an oriented layered structure.
6. The preparation method according to claim 1, characterized in that, A dynamic covalent monomer with a mass fraction of 1-3% is added to the precursor of the second film. The dynamic covalent monomer contains a reversible covalent bond structure, which preferentially breaks and absorbs energy when the material is subjected to mechanical stress or chemical corrosion.
7. The preparation method according to claim 6, characterized in that, The dynamic covalent monomer is selected from dithiodipropionate, 3,4-dihydroxyphenylboronic acid ester, or tetraphenylethylene derivative.
8. The preparation method according to claim 1, characterized in that, The sheet-like filler is selected from one or more of graphene, vermiculite, and montmorillonite, with a particle size of 1-5 μm, a thickness of 5-20 nm, and an aspect ratio of 50-1000.
9. The preparation method according to claim 1, characterized in that, The high-temperature carbonization process is carried out at a temperature of 1050°C, and a protective gas with low oxygen content is introduced throughout the carbonization process.
10. The preparation method according to claim 1, characterized in that, The impregnation filling adopts a vacuum-pressure impregnation process, which includes first evacuating the gas in the pores of the anode plate, then applying positive pressure to make the impregnating agent penetrate into the pores of the anode plate, and finally performing a curing treatment.
Citation Information
Cited By
Green continuous preparation process of chemical modification reinforced composite material
CN121592052A